Rational Combination of Parvovirus H1 With CTLA-4 and PD-1 Checkpoint Inhibitors Dampens the Tumor Induced Immune Silencing - Goepfert, Katrin; Dinsart, Christiane; Rommelaere, Jean; Foerster, Friedrich; Moehler, Markus (Frontiers in Oncology, 2019)
The recent therapeutic success of immune checkpoint inhibitors in the treatment of advanced melanoma highlights the potential of cancer immunotherapy. Oncolytic virus-based therapies may further improve the outcome of these cancer patients. A human ex vivo melanoma model was used to investigate the oncolytic parvovirus H-1 (H-1PV) in combination with ipilimumab and/or nivolumab. The effect of this combination on activation of human T lymphocytes was demonstrated. Expression of CTLA-4, PD-1 and PD-L1 immune checkpoint proteins was upregulated in H-1PV-infected melanoma cells. Nevertheless, maturation of antigen presenting cells such as dendritic cells was triggered by H-1PV infected melanoma cells. Combining H-1PV with checkpoint inhibitors, ipilimumab enhanced TNFα release during maturation of dendritic cells; nivolumab increased the amount of IFNγ release. H-1PV mediated reduction of regulatory T cell activity was demonstrated by lower TGF-ß levels. The combination of ipilimumab and nivolumab resulted in a further decline of TGF-ß levels. Similar results were obtained regarding the activation of cytotoxic T cells. H-1PV infection alone and in combination with both checkpoint inhibitors caused strong activation of CTLs, which was reflected by an increased number of CD8+GranB+ cells and increased release of granzyme B, IFNγ and TNFα. Our data support the concept of a treatment benefit from combining oncolytic H-1PV with the checkpoint inhibitors ipilimumab and nivolumab, with nivolumab inducing stronger effects on cytotoxic T cells, and ipilimumab strengthening T lymphocyte activity.